Professional Learning Communities in Catholic Schools: A Qualitative Exploration for Teacher Professional Development - Wahyudhanti, Theresia Astanti Rorik; Mhunpiew, Nathara; Bistis, Michael (Saengtham College Journal, 2025)
This study explored the characteristics of professional learning communities (PLCs) in Catholic schools and their implications for teacher professional development, particularly in those administered by the Education Department of the Bangkok Archdiocese (EDBA). Using qualitative content analysis of 151 documents, the study identified six features of PLCs within Catholic schools: (1) a shared purpose of student learning, (2) collaborative teams for improved student achievement, (3) reflective collective learning for enhanced professional practice, (4) shared leadership for capacity building, (5) results-oriented learning for sustained improvement, and (6) supportive conditions involving structure, collegiality, and staff capacity. These characteristics align with Catholic educational values emphasizing holistic student formation and communal mission. The findings suggest that PLCs provide a mission-driven framework that integrates ongoing professional growth with faith-based educational goals. Implications for strengthening PLC implementation for teacher professional development within Catholic school contexts are discussed.